DAMPAK SCREEN TIME PADA ANAK USIA 3 TAHUN TERHADAP PERKEMBANGAN SOSIAL-EMOSIONAL DI KB HAJAR ASWAD PACITAN - Nining Pudjiastuti; Endah Wahyu Sugiharti (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2026)
This study aims to analyze the impact of screen time on the social-emotional development of a 3-year-old child at KB Hajar Aswad Pacitan through a case study of a student identified as (R). The research employs a qualitative method with data collection techniques including observation, interviews with teachers and parents, and documentation. The findings indicate that excessive screen time affects social interaction skills, emotional regulation, and responsiveness to the surrounding environment. The subject shows a high interest in digital devices but experiences difficulties in two-way communication, is less responsive to peers, and displays unstable emotions when activities are disrupted. This suggests a relationship between the intensity of screen use and obstacles in early childhood social-emotional development. This study aims to provide an in-depth understanding of the effects of screen time and serve as a reference for parents and educators in managing digital media use wisely to support the optimal development of children’s social-emotional skills.